2011
DOI: 10.1063/1.3600222
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic absorption mechanisms in metal nanospheres: Bulk and surface effects in radiofrequency-terahertz heating of nanoparticles

Abstract: We report on the absorption of electromagnetic radiation by metallic nanoparticles in the radio and far infrared frequency range, and subsequent heating of nanoparticle solutions. A recent series of papers has measured considerable radio frequency (RF) heating of gold nanoparticle solutions. In this work, we show that claims of RF heating by metallic nanoparticles are not supported by theory. We analyze several mechanisms by which nonmagnetic metallic nanoparticles can absorb low frequency radiation, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 29 publications
10
86
0
Order By: Relevance
“…For uncoated neutral GNPs, the heating mechanisms have been discussed extensively in Hanson's work. 15,17 For simplicity, the following model is used to estimate the heating effect in a order of magnitude manner.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For uncoated neutral GNPs, the heating mechanisms have been discussed extensively in Hanson's work. 15,17 For simplicity, the following model is used to estimate the heating effect in a order of magnitude manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, experimentally, Gannon 7 reported that GNP incubated tissue could be heated under 13.56 MHz, resulting in the temperature increase of the malignant tissue by several centigrade. Clearly, this heating effect could not be due to mono-dispersed naked GNPs, whose effects have been disproved both theoretically 17,18 and experimentally. 13,14 There shall have other mechanisms responsible for the reported temperature rise.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…One hypothesis is then that the charged GNPs will facilitate an electrophoretic current that can destroy the cancer under electromagnetic radiation [1,4,5]. However, it is also important to observe the complexity of the clinical application with many possible physical and biophysical phenomena to consider, as well as the fact that several authors have questioned whether metal nanoparticles can be heated in radio frequency at all, see e.g., [1,3]. We have recently performed a study on the physical limitations for radio frequency absorption in a spherical suspension where the main theoretical result is the derivation of an optimal conjugate match with respect to the surrounding medium [4].…”
Section: Introductionmentioning
confidence: 99%